1985
DOI: 10.3168/jds.s0022-0302(85)80847-x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, Characterization, and Regulation of the Prolactin Receptor

Abstract: The prolactin, or lactogenic hormone, receptor has been purified (approximately 80%) from lactating mouse liver and human term placenta by the nondenaturing zwitterionic detergent 3-[(3-cholamidopropyl)-dimethylammonio]-1-propane sulfonate and a prolactin affinity column. The isolated "core-binding unit" has a molecular weight of 37,000 +/- 2,000 daltons. It retains the specificity for lactogenic hormones and binds prolactin with an affinity (Ka = 2 to 6 X 10(9) M-1) similar to that of the receptor as it occur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

1987
1987
2011
2011

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 136 publications
2
15
0
Order By: Relevance
“…A molecular weight of approximately 36,000 and 87,000 for the binding domain is consistent with affinity cross-linking studies using animal tissues [7][8][9]651 and SDS-PAGE analysis of affinity purified material identified by Western blot analysis [66-68 J or probing with 1251-hCH [62,67]. Unidentified bands of these molecular weights have also been seen on coomassie or silver stained gels of affinity purified material including human chorion [5,69].…”
Section: Discussionsupporting
confidence: 65%
“…A molecular weight of approximately 36,000 and 87,000 for the binding domain is consistent with affinity cross-linking studies using animal tissues [7][8][9]651 and SDS-PAGE analysis of affinity purified material identified by Western blot analysis [66-68 J or probing with 1251-hCH [62,67]. Unidentified bands of these molecular weights have also been seen on coomassie or silver stained gels of affinity purified material including human chorion [5,69].…”
Section: Discussionsupporting
confidence: 65%
“…We demonstrated that, during the increased secretion of hCG after 'A and 1 h, the percent age of radiolabeled hCG did not change significantly, either in the intracellular or in the extracellular compart ment. The decreased extracellular secretion of hCG be tween 2 and 24 h, however, was accompanied by a signifi cant decrease in radiolabeled hCG in both compartments at 2, 4, 6, 12 and 24 h. The existence of prolactin receptors in the human pla centa is known [11,12], The action of human prolactin which we observed in our experiments is probably recep tor mediated and therefore very specific. Ovine prolactin failed to have any effect on secretion of hCG.…”
Section: Influence O F Human Prolactin On De Novo Synthesis O F Hcgsupporting
confidence: 42%
“…Proteins were subjected to 10% SDS-PAGE, transferred to Hybond nitrocellulose ECL membrane and probed with mPrlR antibody (M2-5 for EpH4 cells; 1:250 dilution (Vonderhaar et al, 1985); or hPRLR antibody (Invitrogen; 2 μg/ml). Tubulin was used as loading control (Sigma).…”
Section: Western Blot Analysismentioning
confidence: 99%